Secured Auto Encryption and Authentication Process for Cloud Computing Security - Ferdus, Mst Zannatun; Ferdus, Mst Zannatun; Monsur, Md. Hasan; Mst. Jahanara Akhtar; Saiful Islam, (International Journal of Scientific Research and Management (IJSRM), 2024)
In the IT sector, cloud computing is a rapidly expanding technology. Users are being offered more and more flexible and appropriate services by cloud service providers (CSP). Cloud computing users are increasing at a steady pace. Users and CSP are looking for appropriate security measures as cloud computing becomes a need in modern life. A large number of researchers are studying cloud computing security issues. This work introduces an appropriate cryptography and secure user authentication system, which includes auto encryption and a mechanism for updating keys on a cloud site that is not initially accessible to users. After a predetermined amount of time, this operation will recur frequently on the cloud site. This protocol can be carried out manually by CSP at any time, or it can run automatically after a predetermined amount of time. This will guarantee additional data security. Additionally, this procedure adds a level to the user's credentials. Even with legitimate credentials, these feathers will ensure that hackers cannot obtain original files or data. The suggested protocol is emulated by CloudSim, and we saw that there is an additional step requiring user credentials, requiring some time to access files or data for the first time. Although this small amount of time is insignificant and can be disregarded, it significantly improves security.